RESEARCH AND VERIFICATION ON VIBRATION CHARACTERISTICS OF THE SHROUDED TURBINE BLADE - LONG Lun; YUAN Wei; CHENG XiaoMing; TANG ZhenHuan (Jixie qiangdu, 2021)
In order to solve the problem that the accuracy of shrouded blade frequency calculation was reduced due to integrated treatment of shroud working face,the vibration characteristics of shrouded turbine blades were studied.In this paper,a modeling method of shrouded turbine blade considering deformation and actual contact area of shroud working face was proposed.The blade disk modeling and modal analysis were completed by using the above method,and the dynamic stress test was carried out to verify that the first order resonance frequency of the blade calculated by the model is basically consistent with the measured resonance frequency,and the difference between the two is less than 7%. The research work can provide a reference for the vibration design of aero-engine shrouded turbine blade.